Dampak Intervensi Pemberian Suplementasi Mikronutrien terhadap Kesehatan Lansia - Jutomo, Lewi; Galuh Wiedani Kusuma Dyah Larasati; Tadeus Andreas Lada Regaletha (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Currently, the Indonesian nation is experiencing a demographic transition, with a growing elderly population. As they age, they are susceptible to health problems and diseases. Therefore, it is necessary to maintain the health of the elderly by encouraging them to consume micronutrients through supplements and by encouraging them to consume vegetables and fruits. This community service activity aims to evaluate the impact of a one-month micronutrient supplementation intervention on the health of the elderly, including: blood pressure, blood sugar levels, uric acid levels, and cholesterol levels. The method used is a single-group design with a pre-test and post-test approach. The target group consisted of 15 participating elderly people. The activity location is at the Permata Bunda Integrated Health Post, Fatukoa Village, Kupang City. The activity stages include: 1) identifying the target group; 2) preparing micronutrient intervention preparations; 3) pre-test measurements according to predetermined health parameters; 4) implementing the micronutrient supplementation intervention for one month; 5) conducting post-test measurements; and 6) analyzing changes in the results of pre- and post-test measurements. The results of the micronutrient supplementation intervention showed a decrease in systolic blood pressure of -2.67 mmHg, diastolic blood pressure of -1.86 mmHg, blood sugar of -1.96 mg/dL, and uric acid of -0.19 mg/dL, but cholesterol increased by +9.67 mg/dL. This indicates that the micronutrient supplementation intervention has an impact on improving overall health in the elderly except for cholesterol. It is recommended to control cholesterol through consumption of fibrous plant foods such as vegetables and fruits.